PERCHING syndrome: Clinical presentation in the first African patient confirmed by clinical whole genome sequencing. Issue 9 (7th June 2022) - Makay, Prince; Mubungu, Gerrye; Mupuala, Aimée; Bluske, Krista; Brown, Carolyn; Schmidt, Sarah A.; Ngole, Mamy; Fuanani, Patrick; Perry, Denise L.; Lukusa, Prosper; Devriendt, Koenraad; Taft, Ryan J.; et al.
Abstract: PERCHING syndrome is a rare multisystem developmental disorder caused by autosomal recessive (AR) variants (truncating and missense) in the Kelch‐like family member 7 gene (KLHL7) . We report the first phenotypic and molecular description of PERCHING syndrome in a patient from Central Africa. The patient presented multiple dysmorphic features in addition to neurological, respiratory, gastroenteric, and dysautonomic disorders. Clinical Whole Genome Sequencing in the proband and his mother identified two novel heterozygous variants in the KLHL7 gene, including a maternally inherited intronic variant (NM_001031710.2:c.793 + 5G > C) classified as Variant of Uncertain Significance and a frameshift stop gain variant (NM_001031710.2:c.944delG; p.Ser315ThrfsTer23) of unknown inheritance classified as likely pathogenic. Although the diagnosis was only evoked after genomic testing, the review of published patients suggests that this disease could be clinically recognizable and maybe considered as an encephalopathy. Our report will allow expanding the phenotypic and molecular spectrum of Perching syndrome.